Fungal-mediated nanoparticles for industrial applications: synthesis and mechanism of action - Mina Rezghi Rami; Maryam Meskini; Behrouz Ebadi Sharafabad (Elsevier, 2024)
The advancement of safe, eco-friendly, and cost-efficient techniques for nanoparticle production is a crucial objective in nanotechnology. Among the various sustainable methods, the biological synthesis of nanoparticles utilizing fungi, bacteria, yeasts, and plants stands out. Fungi, in particular, are well suited for this task because of their capacity to secrete numerous enzymes and streamline subsequent processes. Using fungal strains for nanoparticle biosynthesis is both technologically appealing and economically viable. The utilization of fungal strains for nanoparticle biosynthesis is both technologically appealing and economically viable. Fungi have long been acknowledged as adept natural engineers capable of creating a wide array of nanoparticles with distinct properties and applications. This article provides an overview of fungus-mediated nanoparticle development, shedding light on the underlying mechanisms of their synthesis and the factors influencing their characteristics. Furthermore, the potential of fungus-mediated nanoparticles in the industrial domain has been explored. These findings emphasize the importance of different fungal species in nanoparticle synthesis, as well as the biocompatibility and environmental friendliness of fungus-mediated nanoparticles. By underscoring the essential role of fungi in connecting natural knowledge with innovative industrial applications, recent progress in enhancing nanoparticle production and optimizing synthesis conditions through fungi has been examined to underscore the feasibility of extensive industrial nanoparticle utilization via fungi.